ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI WAJIB PAJAK ORANG PRIBADI DALAM MEMENUHI KEWAJIBAN MEMBAYAR PAJAK (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Singosari) - Ramadiansyah, Dimas (Jurnal Mahasiswa Perpajakan, 2014)
This study aims to analyze the factors that affect individual taxpayers in meeting their tax obligation. The independent variable in this study is the realization pay tax, service tax authorities, knowledge and understanding of tax laws, the perception of the effectiveness of the tax system. While the dependent variable in this study is the willingness to pay taxes. This study used a nonprobability sampling technique using this type of sampling Incidental sampling. Primary data collection method with questionnaires and secondary data with documents in the collection. Respondents were sampled from the 50 respondents who constitute individual taxpayers and registered with the Tax Office Primary Singosari taxpayer classified as effective. Analysis of the research data using multiple linear regression analysis. Based on the analysis of this study showed that awareness of paying taxes to the value Î²1 = 0.180, the value of the service tax authorities Î²2 = 0.205, knowledge and understanding of tax laws with Î²3 = 0.296 and the value perception of the effectiveness of the tax system with the value of Î²4 = 0.261, respectively variables affect the willingness to pay taxes to the value of a = 1.542. Keywords: Willingness to pay taxes , pay taxes awareness , service tax authorities , knowledge and understanding of tax laws and the perception of the effectiveness of the tax system.